Nitrogen availability determines ecosystem productivity in response to climate warming - Liu, Yang; Men, Mingxin; Peng, Zhengping; Houx, James H., III; Peng, Yunfeng (Ecology, 2022)
One of the major uncertainties for carbon-climate feedback predictions is an inadequate understanding of the mechanisms governing variations in ecosystem productivity response to warming. Temperature and water availability are regarded as the primary controls over the direction and magnitude of warming effects, but some unexplained results signal that our understanding is incomplete. Using two complementary meta-analyses, we present evidence that soil nitrogen (N) availability drives the warming effects on ecosystem productivity more strongly than thermal and hydrological factors over a broad geographical scale. First, by synthesizing temperature manipulation experiments, a meta-regression model analysis showed that the warming effect on productivity is mainly driven by its effect on soil N availability. Sites with a higher warming-induced increase in N availability were characterized by stronger productivity enhancement and vice versa, suggesting that N is a limiting factor across sites. Second, a synthesis of full-factorial warming x N addition experiments demonstrated that N addition significantly weakened the positive warming effect, because the additional N induced by warming may not further benefit plant growth when N limitation is relieved, providing experimental evidence that N regulates the warming effect. Furthermore, we demonstrated that warming effects on soil N availability were modulated by changes in dissolved organic N and soil microbes. Overall, our findings enrich a new mechanistic understanding of the varying magnitudes of observed productivity response to warming, and the N scaling of warming effects may help to constrain climate projections.